Historic Overview of the Extraction of a Multi-reef Shaft Pillar - Lucas, J.; Brentley, K.R. (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
In 1969 Harmony 2 Shaft initiated a partial shaft pillar extraction on the Basal reef due to stress related damage to the shaft and immediate service excavations. Following the partial extraction, deformations in the shaft barrel ceased and normal operations continued. Depletion of the surrounding Basal ore reserve resulted in a re-look at the remaining Basal shaft pillar. However, with the average on-reef principal field stress being in the order of 90 MPa, the pillar was considered “too highly stressed”. A decision was subsequently taken in 1993 to de-stress the remaining Basal pillars by mining the superimposed A-reef shaft pillar situated 140 m above the Basal reef first. This continued until 1995. The slump in the international gold price in 1995 resulted in the majority of the Harmony operations becoming marginal. This prompted an in-depth investigation into the feasibility of mining the remaining Basal shaft pillar, which had an average grade of over 20 g/t. Following extensive modelling exercises, an executive decision was taken to commence the extraction of the remaining Basal pillar concurrently with the overlying A-reef. Extraction of both the Basal and A-reef shaft pillar is 97% complete. The discovery of payable Leader reef in 2005, which is positioned some 20 m above the Basal, has led to the partial extraction of a third reef horizon within the shaft pillar area. This paper highlights the strategic issues pertaining to a multi-reef shaft pillar extraction at depth, focusing on the preparation of the shaft excavation for multi-reef mining, mining sequence, support standards and procedures as well as seismicity experienced during the extraction.